Continuous intraperitoneal insulin infusion as a valuable approach in patients with unstable type 1 diabetes: two case reports and a mini review of the literature - Pedone, Erika; Caretto, Amelia; Belfiori, Giulio; Zanardini, Anna; Di Molfetta, Sergio; Laviola, Luigi; Giorgino, Francesco; Piemonti, Lorenzo; Scavini, Marina; Laurenzi, Andrea (Frontiers in Medicine, 2025)
In recent years, continuous intraperitoneal insulin infusion (CIPII) has become a valid therapeutic option to achieve good glycemic control for patients with unstable type 1 diabetes and subcutaneous insulin resistance, mainly due to the absorption of insulin through the portal venous system. This route improves hepatic uptake and reduces peripheral plasma insulin levels, also optimizing glucagon secretion and hepatic glucose production. CIPII can lead to better blood glucose control and more predictable insulin profiles, especially after meals, compared to subcutaneous injections. Therefore, some studies suggest that CIPII may reduce the risk of hypoglycemia compared to subcutaneous insulin as well as improving patient satisfaction. Actually, among CIPII delivery systems, DiaPort particularly stands out for its low side effects, proven clinical efficacy, and potential for integration into closed-loop systems.